Perceptions regarding the Future of Corporate Social Responsibility in South Africa - Nair, Kubendran (My University, 2012)
The future direction of Corporate Social Responsibility (CSR) in South Africa is uncertain. The literature shows divided views between CSR staying and CSR fading. The literature on the future of CSR is limited with the research focused on identifying possible future scenarios in a global context. This report draws on the previous research into scenarios to explore the future direction of CSR in South Africa as perceived by corporate executives. This report also identifies the challenges that South African companies will face in realising this future and the opportunities that this future will present to them. Semi-structured interviews were conducted with executives of companies in South Africa. Content analysis was used to analyse the data that was collected. Content maps were used to map the conceptual categories and themes that emerged from the data. The key finding is that, firstly, there are two possible future scenarios for CSR in South Africa where the final outcome depends on the uncertainty of whether business will be proactive or reactive to addressing social issues. If South African companies become proactive on social issues, they will partner with government more, society will trust them more, and the economy will benefit. However, if South African companies become reactive on social issues, government will impose further regulations on business, society will lose trust in them, and the economy will suffer. Secondly, eleven challenges are identified to be faced by South African companies with the most commonly identified challenges being leadership, stakeholder alignment, social issues being long term relative to business focus, and resource allocation. Lastly, ten opportunities are identified to be presented to South African companies with the most commonly identified opportunities being brand awareness, employee attraction and retention, employee productivity, government relations, customer loyalty, and addressing the skills gap
MBA thesis - WBS
Keywords: Corporate social responsiblity